Developing The Concepts & Strategy of Smart Regional: How to Increase Tourism & Investors (Smart city 4.0) - Sendi Novianto; Farrikh Alzami; Indra Gamayanto (IJISTECH (International Journal of Information System and Technology), 2021)
Smart city 4.0 is a development of the three previously published articles, namely smart city 1.0,2.0 and 3.0. The smart city article that we created is a long process in research, so we have to make it gradually and make it into several parts. Smart city 1.0 and 2.0 we designed a big picture of a smart city and how the maturity level understood. Next, in smart city 3.0, our focus is on how smart education can be applied in collaboration between each educational institution so that a high-quality level of education achieved in the area. In smart city 4.0, we focus on designing a concept that focuses on developing tourists and how to get investors interested in investing. Factors such as culture, infrastructure/facilities, human resource development in the community, safety and comfort, profit sharing, development of tourist attractions, innovation in improving people's lives and many other factors are our main concern in this article. The methods used in smart city 4.0 are PDCA & USEPDASA, which are both appropriate methods for developing a special framework for tourists and investors. The stages in smart city 4.0 are mapping in terms of culture, human resources, facilities, information technology, security and comfort. These divided into two parts: on the side of increasing tourists and the side of increasing investors. The result of smart city 4.0 is a framework to be able to connect all activities in a smart city to generate profits for the area.